a^2-a-2 = (a-2)(a+1)
a^2-7a+10 = (a-2)(a-5)
So, the first fraction is just (a+1)/(a-5)
a^2-2a-3 = (a-3)(a+1)
a^2+5a+4 = (a+4)(a+1)
So, the 2nd fraction is just (a-3)/(a+4)
Now you have
(a+1)/(a-5) - (a-3)/(a+4)
putting it all over a common denominator of (a-5)(a+4), the numerator becomes
(a+1)(a+4) - (a-3)(a-5)
= a^2+5a+4 - (a^2-8a+15)
= a^2+5a+4-a^2+8a-15
= 13a-11
so (B) is the answer
Homeschooling mom needs help!! Daughter is too smart for me!!!
(a^2-a-2)/(a^2-7a+10)-(a^2-2a-3)/(a^2+5a+4)
A)-3a-11/(a-5)(a+4)
B)13a-11/(a-5)(a+4)
C) -3a+19/(a-5)(a+4)
D)a^2-13a-11/(a-5)(a+4)
3 answers
Thank you Steve! She had the right answer, I was just checking my own thinking. I appreciate the help from all of you, it makes my life a little bit easier. I just wanted to let you know that.
aw, shucks. >scuff scuff<
we aim to please, ma'am.
we aim to please, ma'am.